Structural basis for norovirus inhibition and fucose mimicry by citrate - Hansman, Grant S. (Journal of virology, 2012)
Human noroviruses bind with their capsid-protruding domains to histo-blood-group antigens (HBGAs), an interaction thought to direct their entry into cells. Although human noroviruses are the major cause of gastroenteritis outbreaks, development of antivirals has been lacking, mainly because human noroviruses cannot be cultivated. Here we use X-ray crystallography and saturation transfer difference nuclear magnetic resonance (STD NMR) to analyze the interaction of citrate with genogroup II (GII) noroviruses. Crystals of citrate in complex with the protruding domain from norovirus GII.10 Vietnam026 diffracted to 1.4 Å and showed a single citrate bound at the site of HBGA interaction. The citrate interaction was coordinated with a set of capsid interactions almost identical to that involved in recognizing the terminal HBGA fucose, the saccharide which forms the primary conserved interaction between HBGAs and GII noroviruses. Citrate and a water molecule formed a ring-like structure that mimicked the pyranoside ring of fucose. STD NMR showed the protruding domain to have weak affinity for citrate (460 μM). This affinity, however, was similar to the affinities of the protruding domain for fucose (460 μM) and H type 2 trisaccharide (390 μM), an HBGA shown previously to be specifically recognized by human noroviruses. Importantly, competition STD NMR showed that citrate could compete with HBGA for norovirus binding. Together, the results suggest that citrate and other glycomimetics have the potential to block human noroviruses from binding to HBGAs.